Social-ecological indicators of resilience in agrarian and natural landscapes - Oudenhoven, F.J.W. van; Mijatović, Dunja; Eyzaguirre, Pablo B. (Emerald Publishing Limited, 2011)
The purpose of this paper is to present an approach aimed at facilitating nature conservation that builds on the ecological and social synergies that exist in traditionally managed landscapes in and around protected areas and integrates conservation and social goals to achieve a reduction in the levels of marginalization of indigenous and local communities while preventing ecosystem degradation and biodiversity loss.Drawing on literature research and insights from political and historical ecology and systems theory, a framework was developed to aid the understanding of human‐environment interactions taking place in traditionally managed ecosystems and landscapes and to monitor the role that these interactions play in the maintenance of such systems.Virtually all ecosystems and landscapes must be seen as coupled social‐ecological systems whose ability to respond to stresses and change derives from ecological and social characteristics, as well as from the link between these natural and human components. A variety of mechanisms by which indigenous and rural communities help anchor biodiversity and contribute to social‐ecological resilience were identified.This paper challenges the rationale behind exclusionary approaches to nature conservation. Indicators are developed to facilitate a shift towards the widespread adoption of “human‐centered” conservation practices, in which nature conservation benefits from the inclusion and empowerment of human communities instead of their exclusion and marginalization.